(untitled) (Journal of Partial Differential Equations, 2017)
" In this paper, using the Girsanov transformation argument, we establish Talagrand-type T_2 inequalities under the d_2 metric and the uniform metric d_221e for the law of the solution of a class multivalued stochastic evolution equations."